Optimization of Indonesia-Australia Border Security Operations to Enhance Maritime Security in Support of National Defense - David, Welliam; Sumantri, Rudy; Herman, Juli (AGUSPATI Research Institute, 2024)
One of Indonesia's current maritime challenges is the maritime border with Australia in the Timor Sea and Arafura Sea. This border issue arose after East Timor separated from Indonesia in May 2002. Before East Timor's independence, the Timor Sea and the Arafura Sea served as the waters separating Indonesia and Australia. Several maritime boundary agreements were established between Indonesia and Australia before East Timor's independence. The first was an agreement on certain seabed boundaries signed in 1971 in Canberra. The second was the Timor Gap Treaty in 1989, which addressed issues in the Timor Gap and facilitated cooperation for exploring natural resources in the area. The last maritime agreement between Indonesia and Australia was the Perth Agreement of 1997, which accommodated the Exclusive Economic Zones (EEZ) of both countries in the Timor Sea, Arafura Sea, and Indian Ocean. However, this agreement was not ratified before East Timor gained independence. The maritime boundary dispute between Indonesia and Australia has led to potential traditional and non-traditional threats. The conventional threat involves violations of sovereignty by Australian patrol boats. The Australian government stated that these violations were due to navigational errors by the crew while conducting operations to deter illegal immigrants from entering Australian territory. As for non-traditional security threats, there are three common issues at the Indonesia-Australia border: illegal fishing, exploitation and exploration of natural resources in the Timor Gap, and cross-border crime.